2021
DOI: 10.3389/fpubh.2021.724337
|View full text |Cite
|
Sign up to set email alerts
|

Household Socioeconomic Status and Antenatal Care Utilization Among Women in the Reproductive-Age

Abstract: The study examined the effect of household socioeconomic status and other socio-demographic characteristics on antenatal care (ANC) utilization among 819 women within the reproductive ages across eight rural communities in Delta State, Southern part of Nigeria. Characteristics of the women were described using simple proportion and frequency. The chi-square test was used to examine factors that were significantly associated with a minimum of four (≥4) and eight (≥8) antenatal care contacts, which were respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
2
6
0
1
Order By: Relevance
“…Further, women of low socioeconomic status had higher odds of underutilisation compared with women of high socioeconomic status. This finding is consistent with a recent study in Nigeria 36 where women of high socioeconomic status were more likely to attain the recommended ANC visits. Another study in Myanmar revealed that pregnant women in the highest wealth quintile were three times more likely to attain the recommended eight or more ANC visits compared with women in the lowest wealth quintile.…”
Section: Discussionsupporting
confidence: 93%
“…Further, women of low socioeconomic status had higher odds of underutilisation compared with women of high socioeconomic status. This finding is consistent with a recent study in Nigeria 36 where women of high socioeconomic status were more likely to attain the recommended ANC visits. Another study in Myanmar revealed that pregnant women in the highest wealth quintile were three times more likely to attain the recommended eight or more ANC visits compared with women in the lowest wealth quintile.…”
Section: Discussionsupporting
confidence: 93%
“…However, a number of confounding variables including the quality and regularity of prenatal care and diet that can influence gestational health. Considering these and other such variables were not assessed directly, a latent variable "dem" was constructed using maternal age and SES, as both of these factors are contributory to antenatal care utilization patterns, dietary variables, and pregnancy outcomes (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…This was probably because most of the respondents had an individual source of income since most of them were business and civil servants respectively which made them afford to pay the necessary costs of laboratory tests. These findings were similar to those of a cross-sectional study in Delta State, Southern Nigeria, which revealed that the proportion of respondents who reported ≥ 4 antenatal contacts increases as household wealth quintiles improve (Sui et al, 2021).…”
Section: Maternal Related Factors Affecting Utilization Of Antenatal ...supporting
confidence: 88%